Effect of Soft Drink on Surface Roughness of Preheated and Non-Preheated Nanohybrid Composite Resins - Liliany, Dewi; Violetta, Vanya (Indonesian Dental Association, 2020)
Introduction: Nanohybrid composite resins exhibit a smooth surface due to the presence of small filler particles. Surface roughness is affected by the low pH of soft drinks. A rough surface leads to bacterial adhesion and plaque accumulation, inducing secondary caries. Preheating involves the heating of the composite resin before application, which in turn enhances its properties. Objective: To analyze the difference in the surface roughness of preheated and non-preheated nanohybrid composite resins before and after immersion in soft drinks. Methods: Cylindrical samples of nanohybrid composite resin Filtek™ Z250 XT (10 mm in diameter and 2 mm in height) were prepared and divided into two groups: preheated and non-preheated. For samples in the preheated group, the composite resin was heated using a Micerium SpA heater. All samples were immersed in 10 mL of the soft drink for 2 h per day for 15 days. Surface roughness was measured before immersion and at 12 and 15 days of immersion using the Surface Roughness Tester Taylor Hobson S100 Series. Results: The surface roughness changed at every measurement in each group. Significant differences in the surface roughness of the non-preheated group of the preheated group after 12 days of immersion were not observed. However, a significant difference in the surface roughness of the preheated group after 15 days of immersion was observed. Conclusion: Soft drinks significantly affect the surface roughness of preheated nanohybrid composite resins after 15 days of immersion.